PHD1 controls muscle mTORC1 in a hydroxylation-independent manner by stabilizing leucyl tRNA synthetase - D’Hulst, Gommaar; Soro-Arnaiz, Inés; Masschelein, Evi; Veys, Koen; Fitzgerald, Gillian; Smeuninx, Benoit; Kim, Sunghoon; Deldicque, Louise; Blaauw, Bert; Carmeliet, Peter; Breen, Leigh; Koivunen, Peppi; et al. (Nature communications, 2020)
mTORC1 is an important regulator of muscle mass but how it is modulated by oxygen and nutrients is not completely understood. We show that loss of the prolyl hydroxylase domain isoform 1 oxygen sensor in mice (PHD1 KO ) reduces muscle mass. PHD1 KO muscles show impaired mTORC1 activation in response to leucine whereas mTORC1 activation by growth factors or eccentric contractions was preserved. The ability of PHD1 to promote mTORC1 activity is independent of its hydroxylation activity but is caused by decreased protein content of the leucyl tRNA synthetase (LRS) leucine sensor. Mechanistically, PHD1 interacts with and stabilizes LRS. This interaction is promoted during oxygen and amino acid depletion and protects LRS from degradation. Finally, elderly subjects have lower PHD1 levels and LRS activity in muscle from aged versus young human subjects. In conclusion, PHD1 ensures an optimal mTORC1 response to leucine after episodes of metabolic scarcity. mTORC1 is an important regulator of muscle mass. Here, the authors show that the PHD1 controls muscle mass in a hydroxylation-independent manner. PHD1 prevents the degradation of leucine sensor LRS during oxygen and amino acid depletion to ensure effective mTORC1 activation in response to leucine.